CORPORATE GOVERNANCE AND SUSTAINABLE PERFORMANCE: LESSONS FROM INDONESIA’S HOSPITALITY INDUSTRY - Chris Petra Agung; Wahdan Arum Inawati; Feby Astrid Kesaulya; Yeremias Budi Irawan; Rifky Wardhana Taniwangsa; Rutie Gerda Febriani; Lintang Maheswari Brata (Center for Economic Studies Universitas Katolik Parahyangan, 2026)
This study aims to analyze the effect of board member diversity and earnings quality on the future performance of hotel companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Board diversity is measured by nationality, gender, and expertise; earnings quality is measured by Performance-Adjusted Discretionary Accruals (ADA); and future performance is measured by Return on Assets in the following year. This is a quantitative study using partial least squares-structural equation modeling (PLS-SEM). The results show that board nationality diversity does not significantly affect future performance, indicating that the presence of foreign board members does not fully benefit future performance. Conversely, gender and expertise diversity have a positive and significant effect on future performance. These findings confirm that inclusive representation and professional competence can drive improved company future performance. Earnings quality has a negative effect on future performance. These findings emphasize that transparency and prudence in financial reporting need to be balanced with a more proactive business strategy to drive long-term growth.